2015
DOI: 10.1097/mao.0000000000000891
|View full text |Cite
|
Sign up to set email alerts
|

Management of Geniculate Ganglion Hemangiomas

Abstract: GGHs are rare benign vascular malformations that present with progressive FN palsy. In most patients, early surgical intervention should be considered since shorter duration of FN paralysis and anatomical preservation of the FN are significant predictors of final FN outcome.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
16
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 18 publications
(16 citation statements)
references
References 32 publications
0
16
0
Order By: Relevance
“…Meanwhile, Matthies and Samii found that 17% of patients with vestibular schwannoma had PFP. Peripheral facial palsy was also reported in nearly all cases (113 of 120 [94.2%]) of facial nerve hemangioma reviewed by Oldenburg et al and as an isolated symptom in more than 50% of cases. As reviewed recently by Bacrorn et al, numerous other diseases can mimic BP, a substantial proportion of which (4 of 25 [16.0%]) involve the parotid gland.…”
Section: Discussionmentioning
confidence: 87%
“…Meanwhile, Matthies and Samii found that 17% of patients with vestibular schwannoma had PFP. Peripheral facial palsy was also reported in nearly all cases (113 of 120 [94.2%]) of facial nerve hemangioma reviewed by Oldenburg et al and as an isolated symptom in more than 50% of cases. As reviewed recently by Bacrorn et al, numerous other diseases can mimic BP, a substantial proportion of which (4 of 25 [16.0%]) involve the parotid gland.…”
Section: Discussionmentioning
confidence: 87%
“…Hearing loss and otalgia were less common presentation symptoms, found in 15% and 2% of reported cases, respectively. 2 There is disagreement regarding optimal management of GGH, due in part to the rarity of these lesions. Geniculate ganglion hemangiomas represent 0.7% of all temporal bone tumors, 3 with approximately 130 unique cases reported in the literature.…”
Section: Discussionmentioning
confidence: 99%
“…12 In contrast to facial nerve schwannoma, geniculate ganglion hemangioma is classically associated with more advanced nerve symptoms (including spasm, recurrent palsy with intervals of recovery, or progressive facial paralysis) out of proportion to tumor size. 13 Vertigo and pulsatile tinnitus are rare but may result from invasion of the labyrinth. 14 Facial nerve hemangiomas are typically T1 iso/hypointense, T2 hyperintense, and heterogeneously enhanced on MRI.…”
Section: Discussionmentioning
confidence: 99%